Pendidikan Seks di Sekolah Sebagai Bentuk Perlindungan Dini terhadap Risiko Sosial Anak Perempuan - Theresia Lasmaida Br. Siahaan; Isni Dewinta Manik; Cut Kumala Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Sexual education for children, especially girls, is an important aspect in efforts to protect themselves from social risks such as harassment, violence, and exploitation. This article aims to examine the urgency of integrating sexual education into the basic education system as a strategic preventive measure. The method used is library research by reviewing various scientific literature, reference books, and education policy documents. The results of the study show that many parents still have a wrong understanding of sexual education, so discussions about the body, privacy, and social boundaries are often avoided. In fact, sexual education that is delivered appropriately according to the stages of child development can increase self-awareness, build self-confidence, and strengthen children's communication skills in dealing with risky social situations. Schools have a strategic role as a safe and conducive educational environment in introducing the concept of sexuality in a healthy and responsible manner. Therefore, sexual education should be an integral part of the national curriculum in order to support optimal child growth and development and protect them from various forms of violence.